The Effect Of Religiousness On The Performance Of Outsourced Employees At PT Basirih Industrial Banjarmasin - Luqmanul Hakim; Abdul Gafur; Faqih El Wafa; Ansharullah Ansharullah (Institute of Advanced Knowledge and Science, 2026)
This study aims to determine whether religiosity has a positive and significant effect on the performance of outsourced employees at PT Basirih Industrial Banjarmasin. This research employs a quantitative survey approach. The population in this study is outsourced employees who work in the core production section of PT Basirih Industrial Banjarmasin. The sample in this study amounted to 94 respondents. The sampling technique used was purposive. Data was collected by distributing questionnaires through the Google Form service. The data analysis technique used is a simple linear regression analysis test. Data were analyzed using the SPSS 25 program for Windows. The results of the data analysis showed that the results of the T test obtained a T count (5.178) > T table (1.986) and a significance value of 0.000 < 0.05. Meanwhile, the coefficient of determination test (R-squared) yielded a value of 0.226, equivalent to 22.6%, indicating that the religiosity variable has a 22.6% influence on the performance of outsourced employees.